Pre-Orthodontic Myofunctional Trainers Appliance System: A Review - Afrah Khazal Al Hamdany; Nada Nashee Alhafidh; Lamiaa Abd Ulrhman Hassan (University of Mosul, College of Dentistry, 2022)
Abstract: Malocclusion bearings a great weight internationally. Persistent oral habits produce alteration in the activity of orofacial muscles. Early diagnosis and treatment of the orofacial myofunctional disorders render countless welfares by minimizing related malocclusion and reducing the possibility of relapse after orthodontic treatment. Pre orthodontic trainers are innovative types of prefabricated removable functional appliances claimed to train the orofacial musculature; thus correcting malocclusion. This review aimed to search the literature for studies and case reports on the effectiveness of pre-orthodontic trainers on early correction of developing malocclusion and highlight particularly on its structural characteristics and its mechanism of action. Current literature provides sufficient evidence that these appliances are effective in treating Class II malocclusions especially those due to mandibular retrusion. Case reports on Class I malocclusion have reported relief of anterior crowding, alignment of incisors, and correction of deep bite with pre-orthodontic trainers. Promising results with pre-orthodontic trainers are realized in improved nasal breathing, improved swallowing pattern, and removal of habits like tongue thrusting and mouth breathing.